Spatial effect of a vertical multi-faceted rib on thermal performance and flow characteristics in a square channel - Fithry M.A. (SAGE Publications Ltd, 2024)
A multi-faceted vertical rib has been numerically investigated using the internal flow of rib in a rectangular channel method under turbulent flow for 17,000 < Re < 27,000. The vertical rib that can be encountered inside porous media design often creates a persisting issue of high-pressure drop. The challenge frequently intensifies, mainly when a two-phase state heat transfer is introduced inside the porous media. The vertical multi-faceted rib models the various surfaces often encountered inside the porous media. The effect of blockage ratio on the flow characteristics and thermal performance is observed. The results are compared to the more conventional circular rib, equal in surface area to the multi-faceted rib. The multi-faceted rib yields a higher average Nusselt number of approximately 33% and contributes to the higher average Nusselt number of the channel. The multi-faceted rib channel has a better thermal performance factor, in average of approximately 13% higher and lower pressure drop than the circular rib channel. The advantage of the multi-faceted rib is attributed to, surprisingly, the poor flow attachment on the rib surface, which results in a low Cf/f ratio. Consequently, the multi-faceted rib suffers from very low velocity on the downstream rib surface. Ultimately, the spatial effect of the rib inside the square channel can be evaluated using the Cf/f ratio, which takes into account the rib surface and channel walls. In the quasi two-phase state, the circular rib is observed to provide a more favorable condition for latent heat transfer under extreme condition investigated. IMechE 2022.